Alginate Edible Films Containing Microencapsulated Lemongrass Oil or Citral: Effect of Encapsulating Agent and Storage Time on Physical and Antimicrobial Properties - Bustos-Cerda, R; Matiacevich, S; Alarcon-Moyano, J (Springer India, 2017)
Active edible films have been proposed as an alternative to extend shelf life of fresh foods. Most essential oils have antimicrobial properties; however, storage conditions could reduce their activity. To avoid this effect the essential oil (EO) can be microencapsulated prior to film casting. The aim of this study was to determine the effects of the type of encapsulating agent (EA), type of EO and storage time on physical properties and antimicrobial activity of alginate-based films against Escherichia coli ATCC 25922. Trehalose (TH), Capsul® (CAP) and Tween 20 (Tw20) were used as EA. Lemongrass essential oil (LMO) and citral were used as active agents. The results showed that the type of EA affected the stability of the film forming-emulsions as well as the changes in opacity and colour of the films during storage but not the antimicrobial activity of them. Both microencapsulated EOs showed a prolonged release from the alginate films during the 28 days of storage. Trehalose was selected to encapsulate both active compounds because the films made with this microencapsulated EA showed the greatest physical stability and the lowest color variation among all the films studied. © 2017, Association of Food Scientists & Technologists (India).